On Size Bipartite and Tripartite Ramsey Numbers for The Star Forest and Path on 3 Vertices - Anie Lusiani; Edy Tri Baskoro; Suhadi Wido Saputro (Institute for Research and Community Services (LPPM) ITB, 2020)
For simple graphs G and H the size multipartite Ramsey number mj(G,H) is the smallest natural number t such that any arbitrary red-blue coloring on the edges of Kjxt contains a red G or a blue H as a subgraph. We studied the size tripartite Ramsey numbers m3(G,H) where G=mK1,n and H=P3. In this paper, we generalize this result. We determine m3(G,H) where G is a star forest, namely a disjoint union of heterogeneous stars, and H=P3. Moreover, we also determine m2(G,H) for this pair of graphs G and H.